An exploration of the Lived Mental Health Experiences of psychologists working in the public sector during the COVID-19 pandemic in South Africa - Harvey, Zena (University of the Witwatersrand, Johannesburg, 2023)
The COVID-19 pandemic severely impacted mental health in South Africa, exacerbating the existing mental healthcare treatment gap. Psychologists working at public institutions have been at the forefront of providing mental health care to the public during the crisis. However, psychologists themselves may be considered a vulnerable group at risk of developing adverse mental health outcomes, such as depression, anxiety, burnout and vicarious traumatisation due to the nature of their profession. This vulnerability may have been further amplified during the COVID-19 pandemic. The well-being of psychologists is integral to ensuring high quality patient care and to the overall management of pandemic and other disease outbreaks. There remains a significant dearth in the available literature examining the lived mental health experiences of psychologists, especially those working in the public sector. This study aims to address this pertinent gap by investigating the lived mental health experiences of ten psychologists employed in South African public institutions, amidst COVID-19 pandemic. Semi-structured interviews comprising sixteen questions were conducted with each psychologist. The following five overarching themes emerged from an Interpretive Phenomenological Analysis (IPA): ‘The personal effects of COVID-19 on psychologists’, ‘Changes to therapy During COVID-19’, ‘Experiences of COVID-19 exposure in public hospitals’, ‘Coping Mechanisms’ and ‘Survivor Guilt: Privilege during the pandemic’. A discussion of the abovementioned findings highlighted the importance of addressing, prioritising and monitoring the psychological wellbeing of these public sector-psychologists, during pandemic and other disease outbreaks to increase their support structures.
A research report submitted in partial fulfilment of the requirements for the Degree of Master of Arts in Social and Psychological Research (PSYC7022), to the Faculty of Humanities, in the Department of Psychology, School of Human and Community Development, at the University of the Witwatersrand, Johannesburg, 2023.
Keywords: COVID-19; Public sector; Mental health; Psychologists; South Africa; UCTD; SDG-3: Good health and well-being